PENGUATAN PERAN BUMDES DALAM PEMANFAATAN SAMPAH MENJADI BAHAN BAKAR DALAM RANGKA MENDUKUNG PROGRAM PEMERINTAH MEWUJUDKAN GREEN ECONOMY - Ismail, Ismail; Santoso, Bagus Teguh; Rahmawati, Diana (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2023)
Increasing the green economy-based economy is also a reference as in the SDGs global program (Sustainable Development Goals), turning waste into alternative fuels is a form of support and participation of the community, especially through BUMDES for strengthening government programs in realizing a sustainable green economy. In its implementation, it has multiple effects, including strengthening the village economy as well as stopping environmental pollution due to waste that is not handled with good and sustainable management. This study used a qualitative method with an analytical descriptive approach and participatory rural appraisal (PRA). The trial prototype was carried out in Balun Village, Turi District, Lamongan Regency, East Java Province, involving the Village-OwnedEnterprise "Sumber Mandiri" and the Balun Village Government. The results of this study are that a simple test has been carried out in 2022 in processing plastic waste to produce an alternative fuels to replace Solar, trials were carried out at the research stage of the distillation apparatus, so that based on several findings of deficiencies, in the future it will be repaired and modified so that it can be used in bulk.Keywords: Bumdes, Waste Management, Green Economy.